RESPON ASAP CAIR TEMPURUNG KELAPA DAN PUPUK N, P, DAN K TERHADAP PERTUMBUHAN, FISIOLOGI PADI GOGO - Victor Bintang Panunggul; Ahadiyat Yugi Rahayu; Ismangil Ismangil (University of Prof. Dr. Hazairin, SH, 2021)
The main problem of the minimum that inhibits crop growth, causing low productivity. (1) The study aims determine the effect of liquid smoke coconut oil on growth, of response upland rice physiology, (2) the study aims determine percentage of N, P, K fertilizer on the character of growthand response of upland rice physiology, (3) the study aims determine interaction the effect of variety and liquid smoke coconut oil, and percentage N, P, K fertilizer on the character of growth, and response of upland rice physiology. The research was conducted on April-September 2016 Cendana, Kutasari, Purbalingga. The design used was split – split plot with 3 replications. The main plot is upland rice varieties of Situ Bagendit, Inpago Unsoed 1 and Situ Patenggang. The Subplot is application of coconut shell liquid smoke without application concentration (0,5%), and (1%). The sub-subplot is the dosage of NPK fertilizer percentage of 0% NPK, 25% NPK, 50% NPK and 100% NPK. The variables observed were plant height, leaf number, number of tiller, leaf area, chlorophyll a, chlorophyll b, proline. The results showed that leaf area were significantly different in liquid smoke applications. Plant height, leaf size, chlorophyll b significant of NPK fertilizer.